Respuesta :

Answer:

-(5 n + 6)

Step-by-step explanation:

Simplify the following:

-4 (n + 1) - (n + 2)

-4 (n + 1) = -4 n - 4:

-4 n - 4 - (n + 2)

-(n + 2) = -n - 2:

-4 - 4 n + -n - 2

Grouping like terms, -4 - 4 n - 2 - n = (-4 n - n) + (-4 - 2):

(-4 n - n) + (-4 - 2)

-4 n - n = -5 n:

-5 n + (-4 - 2)

-4 - 2 = -(4 + 2):

-5 n + -(4 + 2)

4 + 2 = 6:

-5 n - 6

Factor -1 out of -5 n - 6:

Answer: -(5 n + 6)

Answer:

D) -5n-6

Step-by-step explanation:

-4(n+1)-(n+2)

-4n-4-n-2

-4n-n-4-2

-5n-4-2

-5n-6